Food and the prison environment: a meta-ethnography of global first-hand experiences of food, meals and eating in custody - Clair Woods-Brown; Kate Hunt; Helen Sweeting (Health & Justice, 2023)
Abstract Background Prison foodways offer a unique opportunity to improve the physical and mental health and wellbeing of an underserved population, yet prison food is often rejected in favour of ‘junk’ food. Improved understanding of the meanings of food in prison is necessary to inform prison food policy and enhance the prison environment. Results A meta-ethnographic synthesis of 27 papers integrated first-hand experiences of food in prison from 10 different countries. The lived experience for most in custody is of poor-quality prison-issued meals, necessarily consumed at a time and place at odds with socio-cultural norms. Beyond nutrition, food carries clear symbolic meanings in prison; through everyday food activities in prison, especially cooking, empowerment, participation, agency and identity are negotiated and performed. Cooking (with others or alone) can reduce anxiety and depression and increase feelings of self-efficacy and resilience in a socially, psychologically, and financially disadvantaged population. Integrating cooking and sharing food into the routine of prison life strengthens the skills and resources available to prisoners, empowering them as they move from the prison environment to the community. Conclusions The potential of food to enhance the prison environment and support improvements in prisoner health and wellbeing is limited when the nutritional content is inadequate and/or where food is served and eaten impacts negatively on human dignity. Prison policy which provides opportunities for cooking and sharing food that better reflects familial and cultural identity has the potential to improve relationships, increase self-esteem, build and maintain life skills needed for reintegration.